Treatment for hydraulic fracturing flowback fluid of shale gas by ceramic membrane-ED-H/L pressure RO process. (April 2023) - Ren, Hong-Yang; Mao, Han; Jin, Wen-Hui; Wang, Jia-Min; Ma, Liang; Wang, Bing
Abstract: The ceramic membrane-ED-H/L pressure RO combined process was constructed for the treatment of fracturing flowback fluid, and the mechanism and influencing factors were investigated. The removal efficiency of TDS and COD reached 97.5 % and 31.9 %, respectively, through coagulation-ceramic membrane which was contaminated slightly by TSS due to the "cross-flow" operation. However, according to the analysis of ceramic membrane by FTIR, SEM and EDS, it was indicated the decreasing of membrane flux would be caused by organic and inorganic composite made from PAM, calcium and barium crystals. The removal of organic pollutants was positively correlated with operating voltage in ED. The removal efficiency of and COD reached 79.3 % on 20 V operating voltage. Based on the analysis of organic matter composition by CG-MS and 3D fluorescence spectroscopy, it was showed the removal efficiency of polar substance, such as phenol, was higher than non-polar substance, such as n-butane due to the electromigration. For the removal of the ions, the removal efficiency of Ca 2+, Mg 2+, Na +, K +, SO4 2− and Cl − reached 99.7 %, 99.6 %, 95.8 %, 99.2 %, 99.3 % and 96.4 % respectively, indicating ion valence had a significant influence on ion removal by ED. The concentrated water and diluted water produced by ED were treated by the RO in high- and low-pressure operation, respectively, in order to improve membrane flux. The COD and TDS were about 11.6 mg/L and 4.0 mg/L in diluted water treated by the RO in low-pressure operation respectively, showing membrane flux hardly decreased significantly with high stability and flux. Graphical abstract: Unlabelled Image